Hubungan Antara Religiusitas dengan Kebahagiaan pada Siswa Siswi di SMA Muhammadiyah 1 Klaten - hapsari, Dea febri, Dr. Wiwien Dinar Pratisti, M.Si (2015)
Any person wishing happiness, as well as teenagers. because not all teenagers happy, one that affects happiness is a religiosity. Happiness is a feeling that is in one's self in the form of positive emotion, a state of positive, positive activities and critical components determining the quality of life of individuals. Many factors influence happiness. This study aims to determine the relationship between religiosity and happiness in adolescents, the level of religiosity in adolescents, the level of happiness in adolescents, and effective contribution to the happiness of religiosity in adolescents. Researchers chose quantitative methods to achieve the objectives of this research. Subjects in this study were Siwa class XI and XII SMA Muhammadiyah 1 Klaten which consists of four classes, namely class XI IPA 3 IPA first XI, XII IPS 1, and XII IPS 2 totaling 75 people. The sampling technique used in this study is a cluster random sampling. The research data was obtained with the scale of religiosity and happiness scale were analyzed using Pearson product moment correlation. Based on the analysis that has been done using the Pearson product moment correlation technique of the obtained results of the correlation coefficient (r) of 0.459 with p value = 0.000 <0.01, which means there is a significant positive relationship between religiosity and happiness in adolescents. based on the results of analysis of religiosity variables have the empirical mean (RE) of 139.33 and the mean hypothetical (RH) of 102.5, which means a relatively high religiosity research subject. Variable happiness have empirical mean (RE) of 74.07 and the mean hypothetical (RH) of 57.5, which means happiness research on the subject is high. Religiosity effective contribution to the happiness of 21%. This suggests religiosity variable variable mempengarugi happiness